Multiple Meningioma Resection by Bilateral Extended Rostrotentorial Craniotomy with a 3D-Print Guide in a Cat - Kyohyuk Song; Haebeom Lee; Jaemin Jeong; Yoonho Roh (Veterinary Sciences, 2022)
A 13-year-old castrated male domestic shorthair cat was referred for the surgical removal of multiple meningiomas. The cat experienced generalized tonic–clonic seizures, altered mentation, mild proprioceptive ataxia, and circling. Magnetic resonance imaging (MRI) revealed two round, solitary, well-delineated, space-occupying lesions suggestive of multiple meningiomas in the right frontal and occipital lobes. Before surgery, patient-specific three-dimensional (3D) printed models and guides were produced using a 3D program based on MRI and computed tomography (CT), and a rehearsal surgery was performed. With a 3D guide to find the location of the craniotomy lines, bilateral extended rostrotentorial craniotomy allowed en bloc resection of multiple meningiomas. The bone fragment was replaced and secured to the skull with a craniofacial plate and screws with an artificial dura. All of the surgical steps were performed without complications. The preoperative presenting signs were resolved by the time of follow-up examinations 2 weeks after surgery. Twelve months after the removal of the multiple meningiomas, the cat survived without further neurological progression. For the resection of multiple meningiomas, surgery can result in large bone defects and risk of massive hemorrhage. For this challenging surgery, patient-specific 3D models and guides can be effective for accurate and safe craniotomies.